Promise and perils of paper-based point-of-care nucleic acid detection for endemic and pandemic pathogens. Issue 5 (23rd January 2023) - Sritong, Navaporn; Sala de Medeiros, Marina; Basing, Laud Anthony; Linnes, Jacqueline C.
Abstract : Review work on the challenges of paper-based NAATs covering sample-to-answer procedures along with the three main types of clinical samples as well as broader operational, scale up, and regulatory aspects of device development and implementation. Abstract : From HIV and influenza to emerging pathogens like COVID-19, each new infectious disease outbreak has highlighted the need for massively-scalable testing that can be performed outside centralized laboratory settings at the point-of-care (POC) in order to prevent, track, and monitor endemic and pandemic threats. Nucleic acid amplification tests (NAATs) are highly sensitive and can be developed and scaled within weeks while protein-based rapid tests require months for production. Combining NAATs with paper-based detection platforms are promising due to the manufacturability, scalability, and simplicity of each of these components. Typically, paper-based NAATs consist of three sequential steps: sample collection and preparation, amplification of DNA or RNA from pathogens of interest, and detection. However, these exist within a larger ecosystem of sample collection and interpretation workflow, usability, and manufacturability which can be vastly perturbed during a pandemic emergence. This review aims to explore the challenges of paper-based NAATs covering sample-to-answer procedures along with three main types of clinical samples; blood, urine, and saliva, as well as broader operational, scale up, and regulatory aspects of device development and implementation. To fill the technological gaps in paper-based NAATs, a sample-in-result-out system that incorporates the integrated sample collection, sample preparation, and integrated internal amplification control while also balancing needs of users and manufacturability upfront in the early design process is required.